PEMANFAATAN KEBUN SEBAGAI SUMBER BELAJAR DENGAN MENERAPKAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) (Journal of Biology Education, 2012)
This purpose of this research was to identify the students’ activities and their learning achievements on the classification of living organism materials by using the Unnes’educational tourism garden as learning resources, integrated in  the JAS  (environmental exploration) approaches for SMP Teuku Umar Semarang students. This research design was  one shot case study. Sample of this research were class VII.1 and VII.3 students  collected by purposive sampling technique. The collecting data methods were questionnaires, documentation, observation sheets and tests. The data were quantitatively measured and descriptively  analyzed. The results showed that 74%-100% of students in three learning activities were classified as active and very active, and 77% of student achieved  optimal student learning outputs (the learning achievement ? 80). Based on the results of research and its discussion it was concluded that Unnes’ educational tourism garden  could be used for a learning resource on the classification of living organism material, integrated in JAS approach  and for optimizing  learning activities and achievements of  SMP Teuku Umar Semarang students. Penelitian ini bertujuan untuk mengetahui aktivitas dan hasil belajar siswa pada pembelajaran materi klasifikasi makhluk hidup dengan memanfaatkan kebun wisata pendidikan sebagai sumber belajar dengan menerapkan pendekatan jelajah alam sekitar di SMP Teuku Umar Semarang. Penelitian ini menggunakan desain the one shot case study. Sampel yang digunakan adalah kelas VII.1 dan VII.3, pengambilan sampel ditentukan dengan teknik purposive sampling. Data dikumpulkan dengan metode angket, dokumentasi, observasi, dan tes. Data-data tersebut dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa 74%-100%  aktivitas belajar siswa tergolong dalam kriteria aktif dan sangat aktif pada tiga kegiatan pembelajaran yang dilakukan, dan 77% siswa hasil belajarnya optimal (nilai hasil belajar ?80). Berdasarkan hasil penelitian dan pembahasan disimpulkan bahwa pemanfaatan kebun wisata pendidikan Unnes sebagai sumber belajar materi klasifikasi makhluk hidup dengan pendekatan jelajah alam sekitar yang diterapkan dapat mengoptimalkan aktivitas dan hasil belajar siswa SMP Teuku Umar.